Value chain development in Nicaragua: prevailing approaches and tools used for design and implementation - Donovan, J.; Stoian, D.; Poe, K. (Practical Action Publishing, 2017)
This article draws on four contrasting cases of value chain development (VCD) in Nicaragua to assess approaches and tools used in design and implementation. We interviewed 28 representatives from the international NGOs leading the interventions, the local NGOs that participated in implementation, principal buyers, and cooperatives. Despite the complexity of market systems, results showed a relatively basic approach to VCD, reflected in: 1) reliance on a single tool for design and implementation; 2) expected outcomes based on technical assistance and training for smallholders and cooperatives; 3) local NGOs and cooperatives with key roles in implementation; and 4) limited engagement with other chain actors, service providers, and researchers.